Simulating longitudinal ventilation flows in long tunnels: Comparison of full CFD and multi-scale modelling approaches in FDS6. (February 2016) - Ang, Chin Ding (Edmund); Rein, Guillermo; Peiro, Joaquim; Harrison, Roger
Highlights: Longitudinal ventilation in a 1.5 km tunnel simulated on Fire Dynamics Simulator. Both full CFD and multi-scale modelling approaches used and compared. Results from multi-scale models similar to full CFD and experimental measurements. Multi-scale approach up to 2.2 times faster than the full CFD approach. Abstract: The accurate computational modelling of airflows in transport tunnels is needed for regulations compliance, pollution and fire safety studies but remains a challenge for long domains because the computational time increases dramatically. We simulate air flows using the open-source code FDS 6.1.1 developed by NIST, USA. This work contains two parts. First we validate FDS6's capability for predicting the flow conditions in the tunnel by comparing the predictions against on-site measurements in the Dartford Tunnel, London, UK, which is 1200 m long and 8.5 m in diameter. The comparison includes the average velocity and the profile downstream of an active jet fan up to 120 m. Secondly, we study the performance of the multi-scale modelling approach by splitting the tunnel into CFD domain and a one-dimensional domain using the FDS HVAC (Heating, Ventilation and Air Conditioning) feature. The work shows the average velocity predicted by FDS6 using both the full CFD and multi-scale approaches is within the experimental uncertainty of the measurements. Although the results showed the prediction of the downstream velocity profile near the jet fan falls outside the on-site measurements, the predictions at 80 m and beyond are accurate. Our results also show multi-scale modelling in FDS6 is as accurate as full CFD but up to 2.2 times faster and that computational savings increase with the length of the tunnel. This work sets the foundation for the next step in complexity with fire dynamics introduced to the tunnel.